Assessing the potential of the transport cum economic corridors in the Greater Mekong Subregion - Kawahara, Hideki; Perret, Sylvain Roger; Babel, Mukand Singh; Shrestha, Sangam; Bohez, Erik L.J.; Electricity Generating Authority of Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Infrastructure, such as transport, electricity and telecommunication, provide us a lot of services in our daily life. Simultaneously, it contributes to increase our standard of living continuously throughout induced economic growth by structural transformations. On the other hand, according to the World Bank estimate, the global population of people living on less than $1 a day was 986 million as of 2004. Most of them are living in developing countries, and provision of infrastructure is extremely limited in those countries. In the recent context of globalization, the demand of regional cooperation has been increasing. Nowadays, most countries cannot manage several issues by themselves because of complex connection to the world. In Asian region, there is the important regional cooperation project that is the Greater Mekong Subregion Economic Cooperation Program. The general objective in this study is to assess the potential of transport cum economic corridors in the GMS. The planning for infrastructure by organization, the similarity among people, the direct impact on provinces and the development process by country were examined as specific objectives. As a result, at first, according to the planning infrastructure by organization analysis, it was revealed that there exist differences of accomplishment state of transport corridors and policies to road network development by country. For example, Thailand had most advanced highway network in this study area and they were shifting away from road construction to management. Moreover, each country has each limitation, such as geographical features, population structure etc. Second, the similarity between and among countries from people's point of view had shown the existence of gaps in terms of culture, economy and climate. For instance, Lao PDR and Thailand had most similarities vise versa PRC and Viet Nam had least similarities in this study area. From this result, we could guess the factors of people's motivation on spontaneous movements, not by government strategies. Third, the result of direct impact analyses on the provinces in Cambodia and Lao PDR have shown that population density had changed along the selected corridors next to the Thailand. In addition to that, most study area had been observed increase of trade and commerce, and tourism related indicators on provinces along the selected corridors. In final analysis, the development process by country was examined by using regression analysis concerning time lag. In Cambodia, the transport corridor development had contributed to job provision and user benefit with time lag. In Lao PDR, however, the transport corridor development had contributed only to job provision. In contrast, Thailand had significant relationship between transport corridor development and user benefit with time lag. The good example was shown in Viet Nam. It showed that almost all development events starting from highway length change had significant relationship. In conclusion, the potential of transport cum economic corridors in the study area were assessed from "Regional Dynamics" point of view by means of following three scenarios. That is to say, "Scenario-1, PRC and Thailand Dominances - Continue to Expand", "Scenario -2: Viet Nam Comes to the Force - Short Term Prospect" and "Scenario -3: Cambodia and Lao PDR Raise Their Heads - Expectation"
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2008
Keywords: Transportation -- Mekong River Region; Roads -- Economic aspects -- Mekong River Region